Value Relevance Atas Informasi Akuntansi Sebelum Dan Sesudah Adopsi IFRS Pada Sektor Aneka Industri - Ferbiana Helena; Juniarti Juniarti Juniarti (Business Accounting Review, 2018)
Theoretically, the value relevance of companies adopting IFRS has many advantages, but there were inconsistencies in previous research results regarding the influence of IFRS adoption on value relevance. This study aimed to prove the influence of IFRS adoption on value relevance. Value relevance is the ability of accounting information in describing the value of the company so that accounting information affects investors' decisions as reflected by changes in stock price. Accounting information is earnings per share (EPS), book value equity per share (BVPS), cash flow from operating per share (CFO / share). The sample in research was miscellaneous industry sector consisted of 22 companies that listed in Indonesia Stock Exchange (IDX) in the period of 2007-2014 with a sample of 176 observations. The data analysis techniques used was panel data with STATA program. This study was conducted by comparing the periods before and after the adoption of IFRS. The results showed that IFRS adoption had a significant positive effect on value relevance.